2008
DOI: 10.1038/nature06445
|View full text |Cite
|
Sign up to set email alerts
|

Sparse optical microstimulation in barrel cortex drives learned behaviour in freely moving mice

Abstract: Electrical microstimulation can establish causal links between the activity of groups of neurons and perceptual and cognitive functions [1][2][3][4][5][6] . However, the number and identities of neurons microstimulated, as well as the number of action potentials evoked, are difficult to ascertain 7,8 . To address these issues we introduced the light-gated algal channel channelrhodopsin-2 (ChR2) 9 specifically into a small fraction of layer 2/3 neurons of the mouse primary somatosensory cortex. ChR2 photostimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
399
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(423 citation statements)
references
References 29 publications
18
399
3
3
Order By: Relevance
“…Spatial specificity of light stimulation can be achieved by two methods: Selective expression of ChR2 in a subset of cells (Adamantidis et al, 2007), or restriction of the illumination to a small region of tissue or even to a single cell . Different strategies for introducing ChR2 into neurons have been used: Viral transfection (Adamantidis et al, 2007;Aravanis et al, 2007;Zhang et al, 2008), in utero electroporation (Petreanu et al, 2007;Huber et al, 2008), and the generation of Thy1 transgenic mice (Arenkiel et al, 2007;Wang et al, 2007). Most of these techniques produce a relatively high density of ChR2 expressing cells, and it is not clear whether individual cells can be activated by focused illumination under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial specificity of light stimulation can be achieved by two methods: Selective expression of ChR2 in a subset of cells (Adamantidis et al, 2007), or restriction of the illumination to a small region of tissue or even to a single cell . Different strategies for introducing ChR2 into neurons have been used: Viral transfection (Adamantidis et al, 2007;Aravanis et al, 2007;Zhang et al, 2008), in utero electroporation (Petreanu et al, 2007;Huber et al, 2008), and the generation of Thy1 transgenic mice (Arenkiel et al, 2007;Wang et al, 2007). Most of these techniques produce a relatively high density of ChR2 expressing cells, and it is not clear whether individual cells can be activated by focused illumination under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although this system made it easy to apply optogenetics to free-moving animals, it is still invasive-wireless headstagemounted systems still need to implant optical fiber into the brain. To reduce invasiveness channels that respond to longer wavelength light have been developed; longer wavelength light penetrates tissue more deeply than short [135][136][137][138][139][140]. Red light-activated opsins such as excitatory red lightactivated channelrhodopsin and inhibitory red-shifted cruxhalorhodopsin (Jaws) can be applied to the surface of the brain or through a thinned skull [119,120].…”
Section: Optogeneticsmentioning
confidence: 99%
“…Previous researchers failed to distinguish the precise neuronal groups associated with learning and memory, while optogenetics provided this possibility. Huber et al (2008) successfully calculated the number of [41,42] 426 neurons necessary for perception by using ChR2 in mouse primary somatosensory cortex and found that optogenetic activation of the targeted neurons apparently elicits associative learning [22] . Interestingly, the same clusters of neurons may display different responses with the same micro-stimulation in different temporal patterns.…”
Section: Application Of Optogenetics In Mammalsmentioning
confidence: 99%